2008
DOI: 10.7748/cnp2008.09.7.7.44.c6682
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced alopecia: a phenomenological study

Abstract: Breast cancer accounts for 16 per cent of all cancers in females. The treatment regimen is complex and almost half of all women with breast cancer undergo alopecia-inducing chemotherapy. The aim of this study was to explore the lived experience of chemotherapy-induced alopecia and its effects on women with breast cancer. Five women who had experienced chemotherapy-induced alopecia in the past 12 months were interviewed, revealing four main and four sub-themes. The findings have implications for health professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 9 publications
0
24
0
3
Order By: Relevance
“…() noted that children might feel peer pressure to have ‘normal’ looking parents. Like the women in this study, women with breast cancer have been found to attempt to shield their children from distress related to the women's alopecia (Power & Condon ).…”
Section: Discussionmentioning
confidence: 98%
“…() noted that children might feel peer pressure to have ‘normal’ looking parents. Like the women in this study, women with breast cancer have been found to attempt to shield their children from distress related to the women's alopecia (Power & Condon ).…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, Baxley, Erdman, Henry, and Roof (1984) agree alopecia is the most traumatic aspect of cancer treatment. These authors also established that alopecia is a life-changing event associated with significant changes in perceived body image (Baxley et al, 1984;Hilton et al, 2007;Kuzbit, 2004;Power & Condon, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Power and Condon (2008) conducted a phenomenological study in which alopecia was described as the most devastating aspect of having cancer. One participant stated she was less prepared for baldness than she was for breast loss.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aspectos psicossociais também foram identificados na referida metassíntese, relacionados aos efeitos do estigma social sucitado pelo câncer de mama 2010a, 2010bBrunet et al, 2013;Cebeci, Yangin, & Tekeli, 2012;Klaeson, Sandell, & Berterö, 2011;Nizamli, Anoosheh, & Mohammadi, 2011;Power & Condon, 2008).…”
Section: O Câncer De Mama: Aspectos Conceituais Epidemiológicos E Terapêuticosunclassified
“…Relataram também sofrimento diante da possibilidade de deixar os filhos órfãos, ainda dependentes dos cuidados maternos (Nizamli et al, 2011). Sobre a alopecia induzida pela quimioterapia, definida como a queda dos cabelos e demais pelos (sobrancelhas, púbis, pernas e braços) (Reis & Gradim, 2018), estudos indicaram que é o efeito colateral mais angustiante (Buki et al, 2016), mais impactante inclusive do que a perda da mama, levando as mulheres a se sentirem infantilizadas quanto à sexualidade pela perda dos pelos pubianos (Power & Condon, 2008) e inseguras quanto à reação dos parceiros íntimos (Nizamli et al, 2011).…”
Section: O Câncer De Mama: Aspectos Conceituais Epidemiológicos E Terapêuticosunclassified